Analysis of particulate matter, carbon emissions and elemental compositions from A diesel engine exhaust fuelled with diesel-biodesel blends / Mohammad Ashraful Alam - Mohammad Ashraful , Alam (2016)
Energy demand is increasing dramatically because of the fast industrial development, rising population, expanding urbanization, and economic growth in the world. To fulfill this energy demand, a large amount of fuel is widely used from different fossil resources. Burning of fossil fuels has caused serious detrimental environmental and health consequences. The application of biodiesel has shown a positive impact in resolving these issues. Biodiesel may derive from either plant or animal sources, and is suitable as a compression ignition fuel in a blend with petroleum diesel. Emissions differences between vehicles operated on biodiesel blends and diesel have investigated previously, but data does not cover the latest engine technologies. This research investigates a comparative regulated emission, particulate matter, carbon emissions and morphological analysis on the exhaust particles emitted from a compression ignition engine using different blending ratios of palm biodiesel at several operating conditions. The physicochemical properties of palm biodiesel and their blends meet the standard specification ASTM D 6751 and EN 14214 standards. A decreasing trend in brake specific fuel consumption and an increasing trend in brake thermal efficiency observed with lower quantity of biodiesel. The maximum brake thermal efficiency attained with diesel fuel and 10% palm biodiesel blend at all condition. Engine emission results showed that the 40% palm biodiesel blend exhibited 6.37% lower amount of brake specific carbon monoxide emissions, and 20% palm biodiesel blend and 40% palm biodiesel blend reduce brake specific hydrocarbon emission at 8.92% and 12.5% respectively. While, nitric oxide emission for the palm biodiesel blends were to be 0.53% to 4.82% higher than diesel fuel. However, the lowest smoke intensity found at 26.2% for 40% palm biodiesel blend compared with diesel fuel. Observed from this experiment; peak particle concentration for 10% palm biodiesel blend at 1200 rpm had 185 cm³ and at 1500 rpm had 212 cm³. A slightly smaller amount of volatile material had found from the biodiesel samples compared to the diesel fuel sample. Thermogravimetric analysis showed that the amount of volatile material in the soot from biodiesel fuels was slightly lower than that of diesel fuel. Palm biodiesel 20% blends reduced maximum 11.26% of volatile matter from the engine exhaust, while 10% palm biodiesel blend reduced minimum 5.53% of volatile matter. On the other hand, the amount of fixed carbon from the biodiesel samples was slightly higher than diesel fuel. Analysis of carbon emissions for 10% palm biodiesel blend reduced elemental carbon had 0.75% to 18%, respectively. Similarly, the emission reduction rate for 20% palm biodiesel blend had 11.36% to 23.46% respectively. While, organic carbon emission rates reduced for 20% palm biodiesel had 13.7% to 49% respectively. Among the biodiesel blends, 20% palm biodiesel exhibited highest oxygen (O) and sulfur (S) concentration, and lowest silicon (Si), and iron (Fe) concentration. Scanning electron microscope images for 20% palm biodiesel showed granular structure particulates with bigger grain sizes compared to diesel. Particle diameter increased under the 2100-2400 rpm speed condition and it was 8.70% higher compared to the low speed conditions. Finally, the results indicated that the composition and degree of unsaturation of the methyl ester present in biodiesel play an important role for reduction in the chemical composition of particulate matter emissions.